Characterization of iron-mediated peroxidative injury in isolated hepatic lysosomes. - Mak, I T (1985)
Peroxidative degradation of the lysosomal membrane and the resultant release of hydrolytic enzymes may be responsible for hepatocellular injury in iron toxicity. In this study, highly purified hepatic lysosomes were exposed to iron salts in vitro; the nature of this iron-mediated process of injury and the susceptibility of the lysosomal integrity were studied. Native hepatic lysosomes from rats were isolated by free flow electrophoresis. Incubation of the lysosomes at 37 degrees C with Fe3+-ADP in the presence of ascorbate resulted in rapid generation of malondialdehyde, which approached a plateau at 20 min. Subsequently, the loss of lysosomal latency, determined as an increased percentage free activity of N-acetyl-beta-glucosaminidase, also occurred and reached a maximum loss at 30 min. The half-maximal level of ascorbate, required to promote the Fe3+-ADP mediated lysosomal peroxidation, was approximately 10 microM; high concentrations of ascorbate were inhibitory and half-maximal inhibition was achieved at a concentration of 2 mM. The iron-mediated lysosomal peroxidation was not inhibited by most active oxygen scavengers and appeared to depend solely on the generation of Fe2+ species. When a fresh solution of Fe2+ was incubated with the lysosomes, both the extent of lipid peroxidation and the degree of latency loss increased as a function of increasing Fe2+ concentration. High concentrations of Fe2+ stimulated lysosomal lipid peroxidation instantaneously and reached the highest level within 10 min; whereas the subsequent maximum loss of latency was achieved within 20 min. Both the MDA formation and the loss of latency in either the Fe3+-ADP + ascorbate or the Fe2+ system were effectively prevented by the presence of vitamin A or vitamin E.